The implementation of standards-based grading - Larson-Reyes, Rebecca (My University, 2013)
As the demands for a higher accountability in our current education system continue to grow, more attention is being given to Standards-based Grading. Based on an abundance of research correlating the positive effects of certain types of feedback and achievement, SBG is a tool that can provide effective feedback and will eventually allow teachers, parents, administrators and government officials to quickly gain quantitative insight concerning student progress in the attainment of specific skills areas. Although not formally recognized as Standards-based Grading, a criterion, skills-based form of grading and assessment has existed for years at the primary level of education. It has only been in the last 15 years that secondary schools have begun to adopt SBG. Considering the future exigencies in education and in hopes of successfully paving the way for my fellow colleagues and other future educators, the purpose of this project was to research, create and implement a standards-based grading system that is both effective and functional at the secondary level. To better illustrate the intricacies of SBG, I have included a 50 minute instructional video, in addition to this paper, that I hope to share with aspiring teachers and fellow colleagues in the future. The video carries the viewer through the processes I executed in rendering an effective tandards-based grading system. It also includes live footage of my 2012 French Level V class with whom I implemented SBG, grading explanations and student interviews.
This file last viewed in Adobe Reader X.
Keywords: Educational evaluation; Grading and marking (Students)